THE EFFECT OF BRAND ENDORSEMENT, E-WOM AND TRUST ON PURCHASING DECISIONS IN E-COMMERCE IN INDONESIA - Dede Suleman; Puji Yuniarti; Dede Mustomi; Roy Irawan; Joko Ariawan; Raden Ati Haryati; Roydawaty; Aprillia (RADJA PUBLIKA, 2023)
In the current era of digitalization, many phenomena often occur in Indonesia, such as the transformation of shopping systems that use more technology and online media. In addition, many young Indonesians like South Korean culture which is synonymous with K-pop music, so companies must be able to see this opportunity as a marketing tool and also the new habit of consumers nowadays is to share their experiences online more often in the form of reviews, recommendations and content. this is a new behavior. Therefore, the purpose of this study is to analyze and test how much influence Celebrity Endorse and E-WOM and trust have on purchasing decisions in e-commerce. This study uses a quantitative method with a descriptive approach and analysis techniques using AMOS SEM. In the results of this study there were 144 respondents 4 variables and 24 indicators which information was processed to meet the research requirements. Statistical test results show that Brand Endorser, E-WOM and Trust have a direct and significant effect on purchasing decisions. And trust is the most influential factor on purchasing decisions.